2007
DOI: 10.1021/la7005309
|View full text |Cite
|
Sign up to set email alerts
|

Layered Inorganic Materials as Redox Agents:  Ferrocenium-Intercalated Zirconium Phosphate

Abstract: The direct intercalation reaction of ferrocene (bis(eta5-cyclopentadienyl)iron(II), Fc) with a highly hydrated layered zirconium phosphate (ZrP) resulted in the formation of the ferrocenium ion (Fc+) within the ZrP material. The Fc+-intercalated ZrP material has an interlayer distance of 10.7 A. The intercalated material was used as an electron acceptor for the oxidation of both ferro-cytochrome c and the excited state of tris(2,2'-bipyridine)ruthenium(II) ([Ru(bpy)3]2+). Upon contact of the material with a 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 77 publications
3
34
0
Order By: Relevance
“…That minimum distance is 4.38 Å when the Cp rings are perpendicular, and the Cp-Mo-Cp angle is parallel, to the ZrP layers. We have previously reported that another metallocene, ferrocene, also intercalates with the Cp rings perpendicular to the ZrP layers [8]. Adding the thickness of a layer of ZrP (6.6 Å) [6,23,24] we would have expected an interlayer distance of 10.98 Å, which is consistent with the 11.0 Å obtained from the XRPD experimental results.…”
Section: Direct Intercalation and Characterizationsupporting
confidence: 87%
See 2 more Smart Citations
“…That minimum distance is 4.38 Å when the Cp rings are perpendicular, and the Cp-Mo-Cp angle is parallel, to the ZrP layers. We have previously reported that another metallocene, ferrocene, also intercalates with the Cp rings perpendicular to the ZrP layers [8]. Adding the thickness of a layer of ZrP (6.6 Å) [6,23,24] we would have expected an interlayer distance of 10.98 Å, which is consistent with the 11.0 Å obtained from the XRPD experimental results.…”
Section: Direct Intercalation and Characterizationsupporting
confidence: 87%
“…Direct intercalation of metallocenes into q-ZrP has not been previously reported in the literature with exception of the direct intercalation of ferrocene for use as a redox agent in our own effort [8].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Thus, a study on the photocatalytic activity of ETS-10 for the conversion of organic substrates with different molecular widths [13], backed up by theoretical analysis of the ETS-10 structure [22], indicates that the pore limiting diameter of ETS-10 is about 5.6 Å. This is almost an exact match with the shortest dimension of the [Fc] þ ion, which can be considered a cylinder with dimensions of 6.8 Å Â 5.65 Å [23]. Indeed, it is known, for example, that the ferrocenium cation can fully penetrate the cavity of the organic host cucurbit [7]uril [24], which has a cavity opening diameter of 5.4 Å [25], to form a highly stable inclusion complex.…”
Section: Introductionmentioning
confidence: 95%
“…Figure 1C shows transmission electron micrographs of α-ZrP nanoparticles with the characteristic hexagonal nano-platelet structure with an average diameter and thickness of ~140 and ~15 nm, respectively. θ-ZrP can be directly ion-exchanged with large metal complexes, producing intercalated phases useful for artificial photosynthesis schemes, amperometric biosensors, vapochromic materials, θ-ZrP can be directly ion-exchanged with large metal complexes, producing intercalated phases useful for artificial photosynthesis schemes, amperometric biosensors, vapochromic materials, catalysis, Catalysts 2017, 7, 132 3 of 14 and drug delivery applications [31][32][33][34][35]. Herein, the layered structure of ZrP is leveraged to support active catalysts for the OER through the ion exchange of transition metal cations.…”
Section: Introductionmentioning
confidence: 99%